Inovasi Desain Kemasan (Packaging) sebagai Faktor Peningkatan Daya Saing Produk UMKM di Desa Ciwarua, Kabupaten Bandung Barat - Carolina Magdalena Lasambouw; Moh Farid Najib; Agustunus Februadi; Tjetjep Djarnika; Wahyu Rafdinal; Neneng Nuryati (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
The purpose of this Community Service (PkM) program is to solve the problems faced by MSMEs for home-based industrial food products in Ciwaruga Village, Parongpong District, West Bandung Regency through assistance in the process of developing product packaging designs produced by MSMEs. Justification for priority issues was developed by optimizing potential through community empowerment through Community Service program support to increase awareness of packaging through surveys of packaging importance, development of appropriate technology and development of marketing networks to increase the competitiveness of MSME home-cooked food products in Ciwaruga Village. The design design of the problem solution implementation method begins with coordination with the Village Head and the Ciwaruga Village Secretary. The output that will be produced from the Community Service program is Appropriate technology, in the form of packaging design/design and a high level of understanding about the importance of packaging through packaging development training.